Identifikasi Waste pada detail Aktivitas Pekerjaan Pembesian - Dwini Teras, Angelina; Rachmawati, Farida (Dinasti Research, 2025)
Waste frequently occurs in construction projects, encompassing both material and non-material waste. This study aims to analyze the waste generated during rebar work, specifically focusing on the detailed activities of measuring and cutting rebar, using the Value Stream Mapping (VSM) approach. The research was conducted at a rebar fabrication facility for a 14-story high-rise building project in Surabaya. VSM was employed to visualize work processes by identifying specific activities in rebar operations, allowing for precise identification of waste. Primary data were collected through direct field observations, while secondary data were obtained from project documents.The findings revealed 11 detailed activities in the measuring process and another 11 in the cutting process. Among these activities, the largest types of waste identified were waiting (10 points), unnecessary motion (6 points), and defects (3 points), totaling 22 waste-related activities. Identifying waste-generating activities and their types in construction work facilitates improved work process efficiency, reduced operational costs, and optimized resource utilization. Furthermore, this also supports enhanced productivity, better work quality, and environmental sustainability by minimizing construction waste.